Restitusi terhadap Anak sebagai Korban Tindak Pidana Perdagangan Orang di Kota Samarinda - Orin Gusta Andini; Aqilza Alyaflah; Grizelda Grizelda (Jurnal Hukum Lex Generalis, 2025)
This research is based on the increase in trafficking cases in the city of Samarinda involving children as victims. Restitution is one of the rights that must be obtained by child victims of sexual violence. Meanwhile, in reality, out of the 20 cases that occurred in the city of Samarinda, there was not a single case that applied Restisui. legal protection for children victims of trafficking in Samarinda still needs a lot of improvement, especially in terms of the implementation of restitution. This study aims to identify and analyze obstacles in the implementation of restitution for children of trafficking victims in Samarinda City. From this case, the problem was formulated, namely, how to implement restitution for child victims of trafficking in the city of Samarinda, and what are the obstacles faced in the implementation of restitution for child victims of trafficking in the city of Samarinda. This research is of the Socio Legal type which was carried out using the statue approach and the case approach. The results of this study reveal that the implementation of restitution for child victims of trafficking in Samarinda City is still far from optimal. Although Law No. 21 of 2007 concerning the Eradication of Trafficking has regulated the right of restitution for victims, as well as the lack of clarity in procedures and the lack of standards in determining the amount of restitution are factors that hinder the implementation of restitution.